Finding the optimal access for proximal upper limb artery (PULA) interventions: Lessons learned from the PULA multicenter registry - Nardai, Sándor; Zafirovska, Biljana; Pataki, Ákos; Nemes, Balázs; Tóth, Júlia; Deák, Mónika; Kedev, Sashko; Bertrand, Olivier Francois; Pirlet, Charles; Merkely, Béla; Ruzsa, Zoltán (Wiley, 2021)
The multicenter proximal upper limb artery (PULA) Registry was created to study the optimal puncture sites for the interventions involving the subclavian, axillary, and innominate arteries.